Production of aluminium-graphite hardener with the use of shaving waste - V. V. Ovchinnikov; A. P. Laskovnev; A. T. Volochko; Zh. E. Makarova (Литьë и металлургия)
The article gives the technology of production of aluminum-graphite hardener with the use of aluminum powders obtained by grinding the aluminum alloys shaving waste.